ANORECTAL MALFORMATION WITH VAGINAL AGENESIS: A CASE REPORT - Nabilla Hardiyanti, Ginanda; Normahayu, Indrastuti; Pradana, Eggy Jita; Widanto (International Journal of Radiology and Imaging, 2023)
Vaginal agenesis is characterised by primary amenorrhea in adolescent women and other abnormalities, such as the absence of the uterus. The incidence of vaginal agenesis or distal vaginal atresia associated with anorectal malformations is difficult to estimate. A 5-year-old patient, at birth, immediately cried, and faeces came out through an orifice in the skin under the vagina. Previously, the patient had planned for a posterior sagittal anorectoplasty (PSARP), but it was known that the patient did not have a vaginal opening at the time of surgery. The patient was diagnosed with a low-type anorectal malformation, vaginal agenesis, and a sigmoidostomy status. PSARP and vaginoplasty were performed while the patient was 7 years old. Clinical and radiographic examination in the first 3 days of age plays a role in determining the type of anorectal malformation and whether or not a colostomy is necessary. In children, MRI radiology plays a role in the preoperative examination to evaluate the size, morphology, and stage of development of the muscular sphincter. Keywords: anorectal malformations, vaginal agenesis.